2018
DOI: 10.7717/peerj.5592
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vineyard soil variability on chlorophyll fluorescence, yield and quality of table grape as influenced by soil moisture, grown under double cropping system in protected condition

Abstract: Environmental factors greatly influence grape quality. Among them, the effect of within-vineyard variability of soil in relation to soil moisture on table grape under protected condition has rarely been studied. In this present research, we investigated the influence of soil variability, in relation with soil moisture on chlorophyll fluorescence, yield and quality attributes of the “Summer Black” (Vitis vinifera L. × V. labruscana L.) table grape, popularly grown under double cropping system in protected cover… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 63 publications
0
9
0
Order By: Relevance
“…The fluorescence of chlorophyll providing different parameters on photosynthetic flows (considered a reliable indicator of plant stress monitoring; [97][98][99]) leads us to the conclusion that in both years there were no excessively limiting situations for plants (no significant differences were found in the two vintages).…”
Section: Discussionmentioning
confidence: 99%
“…The fluorescence of chlorophyll providing different parameters on photosynthetic flows (considered a reliable indicator of plant stress monitoring; [97][98][99]) leads us to the conclusion that in both years there were no excessively limiting situations for plants (no significant differences were found in the two vintages).…”
Section: Discussionmentioning
confidence: 99%
“…Junior et al (2017) showed that the higher values of yield, cluster weight, and titratable acidity (TA) were observed during the summer growing season, whereas the higher values of soluble solids content and pH were observed during winter, which suggested that the grapes harvested during the winter show physicochemical characteristics more suitable than those observed during the summer crops for winemaking purposes in Brazil. However, the winter berries usually had lower cluster weights than the summer berries, thus leading to a lower yield in the winter season (Mitra et al, 2018). Some previous researches reported that the fruitfulness of the second crop of some cultivars, such as "Summer Black, " was much worse in some subtropical areas (Guo et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Ten milliliters of the sample was combined with the indicator bromothymol blue and neutral red and titrated with a 0.1 mol/L NaOH solution. The amount of NaOH (mL) was then converted to tartaric acid (Mitra et al, 2018). Skin from the rest of the 30 berry was manually peeled, immediately frozen in liquid N 2 and stored at −80 °C until further analysis of anthocyanin.…”
Section: Methodsmentioning
confidence: 99%
“…Some approaches were conducted to harvest twice a year not only for table grape production but also for good wine production (Dunuyaali, Okamoto & Shimamura (1983); Lin et al, 1985; Lin, 1987; Favero et al, 2011; Bai et al, 2008; Yan et al, 2014). Recently, for winemaking purposes, the winter fruits in Brazilian showed physicochemical traits more favorable than those from the summer season, because the summer fruits had higher cluster weight and titratable acidity while the winter ones featured a higher total soluble solids (TSS) content and pH value (Junior et al, 2017; Mitra et al, 2018). However, the approaches could not sustainably produce two crops in the following year.…”
Section: Introductionmentioning
confidence: 99%